Dynamic behavior of gas pressure and optimization of borehole length in stress relaxation zone during coalbed methane production. (1st December 2018) - Zhang, Chaolin; Xu, Jiang; Peng, Shoujian; Li, Qixian; Yan, Fazhi; Chen, Yuexia
Abstract: Although coalbed methane (CBM) poses potential safety hazards in coal mines, it can also be used as a clean energy source. Optimization of the borehole length to maximize gas drainage and efficient use of human and material resources are key factors that determine the feasibility and cost of CBM production. In addition, three geo-stress zones are commonly formed in front of the working face due to underground mining activities, namely the stress relaxation zone (SRZ), stress concentration zone (SCZ), and original stress zone (OSZ). In this study, we conducted gas drainage experiments in a simulated SRZ to investigate gas pressure dynamic behavior and optimize the borehole length. The gas pressure gradient in the direction perpendicular to the borehole was greater than that in the direction parallel to the borehole, and the SCZ showed significant hindrance to gas seepage into the borehole. Longer boreholes resulted in higher gas production; however, the gas production increasing rate was not stable over time as the borehole length increased. The relationship between gas production and borehole length is a logarithmic function, which was used to further optimize the borehole length taking mine safety and economic factors into consideration. The following optimized borehole lengths were obtained under experimental conditions: 155.6–262.5 mm, 129.7–155.6 mm, and 24.5–129.7 mm for short-term, medium-term, and long-term gas drainage, respectively.